Assessment of cataract surgery outcomes at Jimma Medical Center, Jimma, Southwest Ethiopia - Atoma Gelalcha, Amare; Bekele, Sisay; Kifle, Dagmawit; Mulatu, Wolela; Kejela Keno, Edosa; Reta Demissie, Wondu (Frontiers in Ophthalmology, 2025)
BackgroundGlobally, cataract is the leading cause of blindness accounting for 51% and affecting approximately 39 million people. Visual rehabilitation is achieved through sight-restoring surgery.ObjectivesThe study aimed to assess the outcomes of cataract surgery that were performed by senior ophthalmologists and residents at Jimma Medical Center (JMC), Jimma, Southwest Ethiopia.MethodsAn institutional-based cross-sectional study was conducted among 341 patients who underwent cataract surgery. The surgery outcomes were assessed using the Physician Quality Reporting System (PQRS) and WHO guidelines. The primary outcomes of the study were post-surgical visual acuity tests, complications within 30 days following surgery, and any additional procedures required. Finally, the outcome of cataract surgery was rated as good, borderline, or poor based on the post-surgical visual acuity test results according to WHO guidelines, and as good vision, no/mild, moderate, or severe visual impairment (VI), and blindness according to PQRS.ResultsOut of the 341 cataract surgeries performed, 171 were operated by residents and 170 by senior ophthalmologists, respectively. The overall prevalence of cataract surgery outcomes based on PQRS guidelines for post-operative visual acuity tests showed good vision in 187 cases (54.8%), no/mild VI in 64 cases (18.8%), moderate VI in 46 cases (13.5%), severe VI in 12 cases (3.5%), and blindness in 32 (9.1%). According to the WHO classification, 253 cases (74.2%) had a good outcome, while 45 cases (13.25%) had a borderline outcome and 43 cases (12.6%) had a poor outcome. The prevalence of cataract surgery outcomes varied among healthcare professionals performing the surgeries. Less than 9.7% of patients required re-surgery within the first month of operation due to complications.ConclusionIn summary, 54.8% of the patients achieved good vision with an acuity test result of 6/12 or better. This finding meets the minimum Medicare PQRS measure value of ≥50% for both professionals. The overall outcome of cataract surgery showed a statistically significant difference between residents and senior ophthalmologists who performed the procedures.